Implementation of Continuity Of Care In Cases of Post Sectio Caesaria - Pratiwi Puji Lestari; Adawiyah Adawiyah (MBUnivPress, 2022)
Pregnancy, childbirth, newborns, postpartum, neonates and the initial visit of family planning acceptors are physiological but in the process there is a possibility that they can threaten the lives of mothers and babies and even death. The maternal mortality rate in Banjarmasin in 2020 did not get any cases of death, but the infant mortality rate in 2020 reached 9 cases. This research method is a case study. This study was to carry out continuous midwifery care for mothers starting from pregnancy and cesarean delivery for indications of placental calcification on continuty of care. Case studies conducted with obstetrics and obstetric care data obtained from the implementation of midwifery management and midwifery documentation. Midwifery care was carried out from a physiological pregnancy, delivery by cesarean section due to indications of placental calcification by ultrasound examination results, the baby was born in good health, the postpartum period did not occur bleeding, there was no infection, lochea expenditure and the uterine involution process were normal, and the mother decided using the mini-pill as a contraceptive method. Midwifery care is carried out for pregnant, maternity and postpartum women as an effort to detect pathological conditions that may occur.